2012
DOI: 10.5430/jhm.v2n4p43
|View full text |Cite
|
Sign up to set email alerts
|

Hematological Malignancies in Chernobyl Clean-Up Workers (1996-2010)

Abstract: Background: Even 25 years after the Chernobyl catastrophe, the interpretation of the findings on leukemia risk among Chernobyl clean-up workers is still a point of much controversy. Precise diagnosis of the main types of hematopoietic malignancies according to FAB classification and new WHO classification may be helpful in estimating the relative contribution of the radiation factor to the overall incidence of such pathologies. Methods:The data on 295 consecutive cases of malignant tumors of hematopoietic and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
22
1

Year Published

2012
2012
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(25 citation statements)
references
References 13 publications
1
22
1
Order By: Relevance
“…The proportion of CLL cases in our study (58%) was higher than the approximately 40% reported by most population-based cancer registries (Dores et al 2007) and 44% of all diagnosed leukemias among males in Ukraine (Gluzman et al 2006). [Note that this number differs from the 29.32% reported in Gluzman et al (2006), which was calculated as a proportion of CLL among all hematological malignancies, including multiple myeloma and NHL.]…”
Section: Discussioncontrasting
confidence: 76%
See 1 more Smart Citation
“…The proportion of CLL cases in our study (58%) was higher than the approximately 40% reported by most population-based cancer registries (Dores et al 2007) and 44% of all diagnosed leukemias among males in Ukraine (Gluzman et al 2006). [Note that this number differs from the 29.32% reported in Gluzman et al (2006), which was calculated as a proportion of CLL among all hematological malignancies, including multiple myeloma and NHL.]…”
Section: Discussioncontrasting
confidence: 76%
“…[Note that this number differs from the 29.32% reported in Gluzman et al (2006), which was calculated as a proportion of CLL among all hematological malignancies, including multiple myeloma and NHL.] An earlier study suggested that cancer registries may be missing as much as 38% of CLL compared with the incidence of CLL detected using sophisticated measures such as flow cytometric immunophenotypic analysis (Zent et al 2001).…”
Section: Discussionmentioning
confidence: 92%
“…The MDS risk existed in atomic bomb survivors from 40 to 60 years after the radiation exposure and showed a significant linear response to exposure dose level (p<0.001) with an ERR of 4.3 per Gy (95% CI: 1.6 to 9.5; p<0.001). The incidence of MDS among the ChNPP accident clean-up workers tended to exceed a respective value among population of Ukraine examined at the same period (4.58 vs. 3.70%) [4]. Monitoring of the cohort of acute radiation syndrome (ARS) survivors in the post-accidental period of the Chornobyl accident at the National Research Centre for Radiation Medicine (NRCRM) was performed since 1986 [5].…”
Section: Introductionmentioning
confidence: 99%
“…Sixteen MDS cases (5.42 %) were revealed among clean-up workers with different forms of leukemia vs. 107 MDS cases (3.70 %) among the patients of Ukraine who were not exposed to radiation [29]. The major MDS forms such as refractory anemia (RA), refractory anemia with ring sideroblasts (RARS), refractory anemia with excess blasts (RAEB), and refractory anemia with excess blasts with transformation (RAEB-T) were delineated according to 1982 FAB classification until 2002.…”
mentioning
confidence: 95%
“…Nevertheless, in several studies, the data on CMML percentage among the patients having been exposed to ionizing radiation are also included. In our earlier study, the percentage of CMML was about the same in both clean-up workers and control groups of the patients [29]. Five CMML cases were recorded in the group of Chernobyl clean-up workers with the median time from 1986-1987 to diagnosis being 14.8 years.…”
mentioning
confidence: 99%